THE RENEWAL CONSTITUTION OF UZBEKISTAN - AN EXAMPLE OF LEGAL CREATIVITY OF OUR PEOPLE - Utemuratov Maxmut Ajimuratovich (International Journal of Law And Criminology, 2023)
The article analyzes that the Constitution, which is a sign of independent statehood, is first of all the face of the nation, the expression of the will of the people, the basis of the development of the society, and that the interests of all layers of the society are taken into account in the new version of the Constitution. Apart from that, issues were considered that indicate that the whole society is united around the idea of building New Uzbekistan, and that our General Assembly is literally becoming the Constitution of the people. Also, the question of what was the necessity of updating the Constitution in some sections of the population and explanations based on relevant factors are discussed.